The effect of immigration on wages in three European countries - Zorlu, Aslan (2002)
We extend the Altonji and Card (1991) framework for analysing the impact of immigrants on natives’ wages from two to three labour types and estimate reduced form wage equations for The Netherlands, United Kingdom and Norway. We find very small effects on natives’ wages and no dominant robust patterns of substitution and complementarity. Effects on wages of earlier immigrants are larger but less reliable. Further work should focus on these own effects.